Counseling gay men, adolescents, and boys : a strengths-based guide for helping professionals and educators - Kocet, Michael M. (New York : Routledge, 2014)
Provides practitioners and educators with critical information needed to help navigate the therapeutic and educational terrain of working with gay males. While other books address a broad range of issues when working with LGBTQ individuals, this volume devotes its focus to the specific needs of gay boys, adolescents, and men. This book also presents an important perspective about individuals who identify as bisexual and transgender, and examines the intersection between gender and sexual orientation --
Part III. Developing integral partnerships in the treatment of gay men, adolescents, and boys -- Assessment and treatment of the medical needs of gay men, adolescents, and boys / James E. Leone, Elizabeth M. Mullin, and Shan Mohammed -- The mental health and counseling needs of gay men, adolescents, and boys / Larry D. Burlew, Nicole Pacheco Pulliam, and Kathleen L. Grant -- The impact of substance abuse and addiction in the lives of gay men, adolescents, and boys / Michael P. Chaney and Michael Brubaker -- Recognizing the needs of sexual minority boys and adolescents in schools / Melissa M. Luke and Kristopher M. Goodrich -- The role of career and leisure needs in the lives of gay men, adolescents, and boys / Jane Goodman and Paul Battle -- Part IV. Counseling special populations : sexual and gender minority boys, adolescents, and men -- Non-gay men and boys : working with men, teens, and boys who identify as bisexual / Jason Patton, Jeff Lubsen, and Stacee Reicherzer -- Counseling in the periphery of queer discourse : transgender children, adolescents, women, and men / Stacee Reicherzer, Andrew S. Garland-Forshee, and Jason Patton.
Includes bibliographical references and index.
Keywords: Gay men -- Counseling of; Gay men -- Mental health; Gay men -- Psychology; Gay teenagers -- Counseling of; Gay teenagers -- Mental health; Gay teenagers -- Psychology